2005
DOI: 10.1042/bj20041842
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inositol phosphorylceramide synthase activity from Trypanosoma cruzi

Abstract: IPC (inositol phosphorylceramide) synthase is an enzyme essential for fungal viability, and it is the target of potent antifungal compounds such as rustmicin and aureobasidin A. Similar to fungi and some other lower eukaryotes, the protozoan parasite Trypanosoma cruzi is capable of synthesizing free or protein-linked glycoinositolphospholipids containing IPC. As a first step towards understanding the importance and mechanism of IPC synthesis in T. cruzi, we investigated the effects of rustmicin and aureobasidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 68 publications
1
44
1
1
Order By: Relevance
“…A similar problem has previously been identified with the use of Trypanosoma cruzi derived microsomes in an assay of TcIPCS turnover (Figueiredo, et al 2005 ). However, it has been demonstrated that washing microsomal membranes derived from the pathogenic yeast, Candida albicans with a zwitterionic detergent (CHAPS) removed endogenous substrate lipids without affecting IPCS activity (Aeed, et al 2004).…”
Section: Assay Of Lmjipcs Microsomal Materialsmentioning
confidence: 90%
See 2 more Smart Citations
“…A similar problem has previously been identified with the use of Trypanosoma cruzi derived microsomes in an assay of TcIPCS turnover (Figueiredo, et al 2005 ). However, it has been demonstrated that washing microsomal membranes derived from the pathogenic yeast, Candida albicans with a zwitterionic detergent (CHAPS) removed endogenous substrate lipids without affecting IPCS activity (Aeed, et al 2004).…”
Section: Assay Of Lmjipcs Microsomal Materialsmentioning
confidence: 90%
“…These data provide the first direct indication of the mechanism of action of the sphingolipid synthase family. Such analyses would not have been possible using a conventional assay system such as that previously employed for the T. cruzi orthologue (Figueiredo, et al 2005). However, by employing a complemented yeast system, large quantities of active LmjIPCS could be isolated in a cost effective manner avoiding the handling of pathogenic material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transfer reaction is catalyzed by the phosphatidylinositol: ceramide phosphoinositol transferase (IPC synthase), a membrane-bound enzyme [11,12]. In S. cerevisiae and C. albicans, phytoceramide is the preferred receptor for phosphoinositol.…”
mentioning
confidence: 99%
“…The assay mix contained 100 µM donor substrate (bovine liver PI, PC or PE, Avanti Polar Lipids), 10 µg of microsomes, 100 mM Tris HCl, 10 mM EDTA, 6 mg/ml BSA and 5 µM NBD C 6 -ceramide [19]. Following incubation at 30 °C for 60 minutes the reaction was quenched by the addition of 150 µl of chloroform:methanol:water (10:10:3).…”
Section: Metabolic Labelling and Analysesmentioning
confidence: 99%